Towards Cancer Theory – Circadian and 11-Day Biological Clocks - Yuri Kirsta (Shiraz University of Medical Sciences, 2021)
Background: In the current study, we used the information-hierarchical system approach to examine human metabolism. Metabolism hierarchical structure, beginning from enzyme level, is controlled by the established information principle and divine section numbers. This structure represents a key mechanism of the hierarchical biological clock (HBC) of human body. Time cycles of HBC hierarchical levels are nested into each other according to strict dynamics schemes. The cycles form the HBC scales of 1, 6, 42 seconds, 24 hours (circadian rhythm), and 11 days and jointly make up the precision HBC similar to the conventional countdown (1 s, 1 m, 1 hr, 1 day, and 1 month). Method: Diagnostic/prognostic studies of cancer require a detailed analysis of metabolic HBC disorders. We utilized the information-hierarchical system approach and the information principle in order to analyze HBC run under different dietary patterns. Results: We characterized hierarchical metabolic systems with 24-hour and 11- day operation times. The 24-hour circadian rhythm comprised citrate, pentose, and fatty acid (anabolic or catabolic) biochemical cycles individually. The 11-day cyclicity referred to these cycles combined into a ternary system of the higher-rank hierarchical level. Disorder of systems operation should lead to a radical change in HBC run with subsequent transformation of normal cells into cancer cells. Conclusion: Mutations of metabolic enzyme genes can damage HBC run, thereby leading to cancer and other chronobiological disorders. Organized rhythmicity of external factors (everyday food intake, 11-day periodical dietary pattern, and so forth) made it possible to heal cancer cells per se. Applying a particular kind of diet, the human lifespan could significantly increase. The proposed direction of cancer prevention and treatment can be called a cancer metabolism chronotherapy.